2008
DOI: 10.1016/j.immuni.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Lytic Granule Loading of CD8+ T Cells Is Required for HIV-Infected Cell Elimination Associated with Immune Control

Abstract: SUMMARY Virus-specific CD8+ T cells probably mediate control over HIV replication in rare individuals, termed long-term nonprogressors (LTNPs) or elite controllers. Despite extensive investigation, the mechanisms responsible for this control remain incompletely understood. We observed that HIV-specific CD8+ T cells of LTNPs persisted at higher frequencies than those of treated progressors with equally low amounts of HIV. Measured on a per-cell basis, HIV-specific CD8+ T cells of LTNPs efficiently eliminated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
584
3
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(641 citation statements)
references
References 47 publications
52
584
3
2
Order By: Relevance
“…By 1 wk following Treg depletion, significantly more activated CD8 + T cells from lymph nodes and spleen expressed granzyme B (Fig. 2C), a cytotoxic molecule known to be important in immune control of both FV (20) and HIV (21). This was also found for the subset of tetramer-positive CD8 + T cells recognizing the immunodominant FV epitope (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…By 1 wk following Treg depletion, significantly more activated CD8 + T cells from lymph nodes and spleen expressed granzyme B (Fig. 2C), a cytotoxic molecule known to be important in immune control of both FV (20) and HIV (21). This was also found for the subset of tetramer-positive CD8 + T cells recognizing the immunodominant FV epitope (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…45 Although not confirmed by real-time PCR, TAP1 was also up-regulated in the noncontrollers in the array analysis. Surprisingly, although having a more potent granzyme B-mediated cytolytic CD8 ϩ T-cell activity against HIV-infected CD4 ϩ T cells is thought to be a feature of viral controllers, 8 expression levels of granzyme K were significantly higher in the noncontrollers. In aggregate, these results suggest that, even though HIV-specific CTL activity may be enhanced in viral controllers, 8 the mucosal microenvironment of noncontrollers displays broad activation of host antiviral mechanisms.…”
Section: Verification Of Gene Expression By Real-time Pcr Analysismentioning
confidence: 99%
“…Recent reports have shown that these persons (1) have a higher frequency of polyfunctional HIV-specific CD4 ϩ and CD8 ϩ T-cell responses in the peripheral blood and in gut-associated mucosal lymphoid tissues (GALT), [5][6][7] (2) present highly potent granzyme B-mediated cytolytic CD8 ϩ T-cell activity against HIV-infected CD4 ϩ T cells, 8 (3) display decreased expression of immunoregulatory receptors that negatively impact upon CD4 ϩ T-cell function, 9 (4) are enriched for protective class HLA haplotypes, 6,10 and/or (5) harbor HIV virions with reduced fitness. 11 There is, however, no individual factor that appears to be common to all controllers.…”
Section: Introductionmentioning
confidence: 99%
“…However, the cytokine secretion and cytolytic functions are not exclusive to either cell subset (19)(20)(21). IFN-g and TNF-a secretion as well as cytolysis have documented antiviral activity and are functions attributable to both NK and CD8 + T cells (18,(22)(23)(24)(25)(26)(27). In HIV infection, where there is evidence that CD8 + T cells play a role in controlling virus, it is not so much the frequency or breadth of epitope recognition by these T cells, but rather the functional quality of their anti-HIV responses that correlates best with VL control (28,29).…”
mentioning
confidence: 99%